Overt Lower Gastrointestinal Bleeding and Pseudotumor: A Rare Presentation of Cytomegalovirus Infection - Akanksha Agrawal; Deepanshu Jain; Sameer Siddique (Case Reports in Medicine)
Cytomegalovirus (CMV) is a ubiquitous organism which can infect multiple organs of the body. In an immunocompromised patient, it can have a myriad of gastrointestinal manifestations. We report a case of recurrent hematochezia and concomitant pseudotumor in an AIDS (acquired immunodeficiency syndrome) patient attributable to CMV infection. A 62-year-old man with a history of AIDS, noncompliant with highly active antiretroviral therapy (HAART), presented with bright red blood per rectum. Index colonoscopy showed presence of multiple ulcers, colonic stenosis, and mass-like appearing lesion. Biopsy confirmed CMV infection and ruled out malignancy. Cessation of dual antiplatelet therapy and compliance with HAART lead to clinical cessation of bleeding and endoscopic healing of ulcers with complete resolution of colon mass on follow-up colonoscopy.